Protecting Student Anonymity in Research Using a Subject-Generated Identification Code - Lippe, Megan; Johnson, Bailey; Carter, Patricia (Journal of professional nursing, 2019)
Within nursing education research, protection of students as human subjects must be the highest priority. This protection can be provided via student anonymity. A subject-generated identification code, comprised of responses to a series of questions, can link data across time points while protecting student anonymity. Two studies, focused on palliative care education, used a subject-generated identification code to link student data across multiple time points. Refinements to the code were made between studies to further enhance anonymity and response consistency. The subject-generated identification code fostered linking of student responses across three time points in study one and two time points in study two. There are many benefits to utilizing a subject-generated identification code in nursing education studies. Researchers must consider the need for a data management expert and balancing transposition errors and the power to differentiate between responses. •Educational research with students risks power differentials.•Protection of student anonymity can mitigate the power differential.•A subject-generated identification code facilitates anonymous student survey completion.•Data can still be linked across time points.•Educational researchers should use subject-generated identification codes in research.